Tunable Superconductivity in Phosphorus‐Doped Topological Transition‐Metal Germanide Mo5Ge3. Issue 12 (26th October 2022) - Xiao, Guorui; Ji, Liangwen; Yang, Wuzhang; Zhu, Qinqing; Song, Shijie; Cao, Guang‐Han; Ren, Zhi
Abstract: The effect of phosphorus doping in the transition metal germanide Mo5 Ge3, which is predicted to be a nodal line semimetal and exhibits superconductivity below T c = 0.75 K, is studied. It is found that Mo5 Ge 3 − x _3-x P x retains the tetragonal W5 Si3 ‐type structure up to x = 1.0, and the incorporation of phosphorus leads to a shrinkage of the unit cell volume. Remarkably, T c of Mo5 Ge 3 − x _3-x P x is enhanced by more than one order of magnitude with increasing x, reaching 8.24 K at x = 1.0. This enhancement is attributed to the increases in both the density of states at the Fermi level and electron–phonon coupling strength. Theoretical calculations show that the phosphorus doping leads to a nearly rigid‐band shift of the Fermi level into a local maximum of the density of states. This study unveils that transition metal germanides offer an emerging platform to study the interplay between superconductivity and nontrivial band topology. Abstract : Phosphorus doping in the nodal line semimetal Mo5 Ge3 induces a strong enhancement of its T c from 0.75 to 8.24 K. This enhancement is attributed to the increases in both the Sommerfeld coefficient and electron–phonon coupling strength, resulting from to a nearly rigid‐band shift of the Fermi level into a local maximum of the density of states.